Development of Comics Media to Improve Science Literacy and Concepts Understanding Junior High School Students In Central Halmahera Regency Through Reading Literacy Program - Ade, Risnawati; Nasichah , Arini Z.; Mas'ud, Abdu (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
In the era of globalization and information technology that continues to develop, the world of education must be able to adapt to various changes. One very important aspect of the world of education is the use of learning media. This study aims to determine whether the development of learning media in the form of comics based on scientific literacy and students' conceptual understanding developed in this study is suitable for use in the learning process at SMP Negeri 4 Halmahera Tengah through the reading literacy program and to determine whether learning media in the form of comics can improve scientific literacy and students' conceptual understanding at SMP Negeri 4 Halmahera Tengah through the reading literacy program. This research is a type of development research (Research and Development). The data collection technique used in this study is to use five stages, namely the Define Stage, Development Stage, Interview, Observation, and Response Questionnaire. The study's data sources are divided into two parts, namely qualitative and quantitative data. Data analysis techniques in the study used the One-Group Pretest-Posttest Design, T-Test, and N-Gain Test. The study results showed that: 1) Regarding validity, the total percentage of the average value of media and material experts was 96%, categorized as